Immunostaining of βA-Activin and Follistatin Is Decreased in HPV(+) Cervical Pre-Neoplastic and Neoplastic Lesions - Victor Jesus Huaringa Payano; Lara Verônica de Araújo Lopes; Larissa Rodrigues Peixoto; Keila Alves da Silva; Tania Maria Ortiga-Carvalho; Alexandre Tafuri; Annamaria Ravara Vago; Enrrico Bloise (Viruses, 2023)
The activin–follistatin system regulates several cellular processes, including differentiation and tumorigenesis. We hypothesized that the immunostaining of βA-activin and follistatin varies in neoplastic cervical lesions. Cervical paraffin-embedded tissues from 162 patients sorted in control (n = 15), cervical intraepithelial neoplasia (CIN) grade 1 (n = 38), CIN2 (n = 37), CIN3 (n = 39), and squamous cell carcinoma (SCC; n = 33) groups were examined for βA-activin and follistatin immunostaining. Human papillomavirus (HPV) detection and genotyping were performed by PCR and immunohistochemistry. Sixteen samples were inconclusive for HPV detection. In total, 93% of the specimens exhibited HPV positivity, which increased with patient age. The most detected high-risk (HR)-HPV type was HPV16 (41.2%) followed by HPV18 (16%). The immunostaining of cytoplasmatic βA-activin and follistatin was higher than nuclear immunostaining in all cervical epithelium layers of the CIN1, CIN2, CIN3, and SCC groups. A significant decrease (p < 0.05) in the cytoplasmic and nuclear immunostaining of βA-activin was detected in all cervical epithelial layers from the control to the CIN1, CIN2, CIN3, and SCC groups. Only nuclear follistatin immunostaining exhibited a significant reduction (p < 0.05) in specific epithelial layers of cervical tissues from CIN1, CIN2, CIN3, and SCC compared to the control. Decreased immunostaining of cervical βA-activin and follistatin at specific stages of CIN progression suggests that the activin–follistatin system participates in the loss of the differentiation control of pre-neoplastic and neoplastic cervical specimens predominantly positive for HPV.